Enhancing Data Integrity A Study on JWT Implementation in Backend API for E-Presence Systems - Wahyu Sholeha, Eka; Fathurrahmani, Fathurrahmani; Noor, Agustian; Herpendi, Herpendi; Anwar Hafizd, Khairul; Habibi, Afrizal; Maireza, Muhammad (Bahasa Indonesia, 2024)
This research delves into the realm of data integrity enhancement within E-Presence Systems by conducting a comprehensive study on the implementation of JSON Web Token (JWT) in the backend API. The use of JWT as an authentication and authorization mechanism aims to fortify the security posture of E-Presence Systems, ensuring reliable and tamper-resistant data transactions. The study investigates the impact of JWT on data integrity, exploring its role in preventing unauthorized access and mitigating potential security vulnerabilities. Through empirical analysis and practical implementation, this research sheds light on the efficacy of JWT in safeguarding the backend API of E-Presence Systems, thereby contributing to the evolution of secure and resilient electronic presence solutions.